Transfascial suture fixation technique in laparoscopic repair of inguinal hernia - Chan, Shun‐Yan B (Asian J Endosc Surg, 2019)
INTRODUCTION: This study presents the initial results of a transfascial suture mesh fixation technique. This method was devised to reduce operative costs and foreign body‐associated risks while embracing the benefits of fixation in laparoscopic inguinal hernia repair. MATERIALS AND SURGICAL TECHNIQUE: Patients undergoing laparoscopic inguinal hernia repair with transfascial suture fixation (TRANSFIX) in our center between March 2017 and March 2018 were retrospectively reviewed. The procedure is orchestrated by a reusable fascial closure device sequentially puncturing the fascia vertically through the inferior port site and guiding a polypropylene thread through the mesh. The thread is retrieved from the extraperitoneal plane with the device, creating an extracorporeal suture loop to embed a surgical knot at the subcutaneous layer of the port site. DISCUSSION: In its first year after introduction, 16 TRANSFIX were performed. All patients were men (mean age, 62.6 years). Thirteen hernias (81.3%) were first occurrence, and three (18.8%) were recurrent. Twelve (75.0%) were direct hernias, and three (18.8%) were indirect hernias; one patient presented with concurrent direct and indirect hernia. Median operating time was 41.5 minutes for unilateral repair and 73.0 minutes for bilateral. Median blood loss was 5 mL. One patient had a seroma after unilateral indirect hernia repair. After a median follow‐up of 15.5 months (range, 9‐21 months), no patient had chronic pain, wound infection, hematoma, or recurrence. Instrumental cost reduction per operation was between $150 and $300. TRANSFIX appears to be a safe and economical mesh fixation method.